ANALYSIS OF CATCH-FISHERIES MANAGEMENT AFTER TSUNAMI - Nahib, Irmadi (Badan Informasi Geospasial, 2008)
The earthquakes and tsunamis often occurred in Indonesia. An impact of these unwanted natural disaster was predicted to increase the number of poor fishermen and to decrease their welfare. This prediction is not absolutely true. However, a proper application of economic policy on fisher after earthquakes and tsunamis can be a momentum to improve fishermens welfare in the long term. The objective of this paper is to study the impact of earthquakes and tsunamis to fishermenâs welfare based on theory of marine economic resources. After Earthquakes is expected to increase the stock of fisheries, which will lead to improvement of fishermenâs prosperity in the future.Keyword: Fisheries, Management, Bioeconomic, Earthquakes, Tsunami, PangandaranABSTRAKGempa bumi dan tsunami sering terjadi di Indonesia. Dampak bencana alam yang tidak diinginkan ini diperkirakan akan meningkatkan jumlah nelayan miskin dan mengurangi kesejahteraan nelayan. Prediksi ini tidak sepenuhnya benar. Namun, aplikasi yang tepat dari kebijakan ekonomi perikanan paska gempa bumi dan tsunami dapat menjadi momentum untuk memperbaiki kesejahteraan nelayan dalam jangka panjang. Tujuan penulisan makalah ini adalah untuk mempelajari dampak gempa bumi dan tsunami terhadap kesejahteraan nelayan berdasarkan teori sumber daya ekonomi (laut). Pasca gempa bumi diperkirakan akan meningkatkan stok perikanan, yang akan mengarah pada peningkatan kesejahteraan nelayan di masa depan.Kata Kunci: Perikanan, Manajemen, Bioeconomi, Gempa Bumi, Tsunami, Pangandaran.